Implementasi Constitutional Complaint Sebagai Perluasan Kewenangan Mahkamah Konstitusi Dalam Penyelesaian Pelanggaran Kode Etik Profesi Hakim - Putri, Maria Sylvia; Ardiana, Oktavia Dwi; Azzahra, Dinda; Harsanti, Khairunnisa Putri; Humaira, Hana (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This article discusses the implementation of constitutional complaint as an expansion of the authority of the Constitutional Court (MK) in resolving violations of the professional code of ethics of judges in Indonesia. This research is motivated by the crucial role of judges as law enforcers and guardians of justice, where violations of the code of ethics by judges can undermine public confidence in the justice system. Although the Judicial Commission (KY) has a role in supervising and recommending sanctions against judges, its authority is limited to administrative sanctions and has not been able to address the constitutional rights of aggrieved citizens. This legal vacuum, coupled with the low follow-up of KY sanction recommendations by the Supreme Court, suggests the urgency of a new mechanism. Based on Robert Alexy's theory of constitutional rights, the absence of a constitutional complaint hinders the protection of citizens' constitutional rights, especially when violations are committed by judges. The concept of constitutional complaint, applied in countries with civil law legal systems and similar constitutional jurisdictions such as Austria and South Korea, offers a solution as a last resort to protect constitutional rights from unconstitutional state actions or court decisions. Therefore, this study recommends the expansion of the Constitutional Court's authority through the revision of Law Number 24 of 2003 concerning the Constitutional Court to include a constitutional complaint, as a concrete step in protecting the constitutional rights of citizens and strengthening the role of the Constitutional Court as the guardian of the constitution.